Piety, politics, and everyday ethics in Southeast Asian Islam: beautiful behavior - Rozehnal, Robert Thomas (Bloomsbury Academic, 2019)
The interplay between adab and local ethics and etiquette in Indonesian and Malaysian literature / Muhammad Ali -- "Young people are seeking their blessings" : Islamic life courses, explorative authority, and the possibilities of worldly adab in rural Aceh / Daniel Andrew Birchok -- Adab and the culture of political culture / Thomas Pepinsky -- Sharia, adab and the Malaysian state / Timothy P. Daniels -- Women's adab in the pesantren : gendering virtues and contesting normative behaviors / Nelly van Doorn-Harder -- Politicians, pop preachers, and public scandal : a personal politics of adab / James B. Hoesterey -- Adab and embodiment in the process of performance : Islamic musical arts in Indonesia / Anne K. Rasmussen -- Smoke, fire and rain in Muslim Southeast Asia : environmental ethics in the time of burning / Anna M. Gade